Phenotypic Characterization of CD4+ T Lymphocytes in Periportal Fibrosis Secondary to Schistosomiasis - Santana, Jordana Batista; de Almeida, Tarcísio Vila Verde Santana; Lopes, Diego Mota; Page, Brady; Oliveira, Sergio Costa; Souza, Irismá; Ribeiro, Luís Eduardo Viana Silva; Gutiérrez, Néstor Adrián Guerrero; Carvalho, Edgar M.; Cardoso, Luciana Santos (Frontiers in Immunology, 2021)
Schistosomiasis is a parasitic disease that affects about 166 million people around the world. It is estimated that 5-10% of individuals with schistosomiasis develop severe forms of the disease, which are characterized by pulmonary hypertension, ascites, periportal fibrosis, and other significant complications. The chronic phase of the disease is associated with a Th2 type immune response, but evidence also suggests there are roles for Th1 and Th17 in the development of severe disease. The aim of this study was to evaluate the CD4+ T lymphocyte profile of patients with different degrees of periportal fibrosis secondary to schistosomiasis. These individuals had been treated for schistosomiasis, but since they live in a S. mansoni endemic area, they are at risk of reinfection. They were evaluated in relation to the degree of periportal fibrosis and classified into three groups: without fibrosis or with incipient fibrosis (WF/IFNE), n=12, possible periportal fibrosis/periportal fibrosis, n=13, and advanced periportal fibrosis/advanced periportal fibrosis with portal hypertension, n=4. We observed in the group without fibrosis a balance between the low expression of Th2 cytokines and high expression of T reg cells. As has already been described in the literature, we found an increase of the Th2 cytokines IL-4, IL-5 and IL-13 in the group with periportal fibrosis. In addition, this group showed higher expression of IL-17 and IL-10 but lower IL-10/IL-13 ratio than patients in the WF/IFNE group. Cells from individuals who present any level of fibrosis expressed more TGF-β compared to the WF/IFNE group and a positive correlation with left lobe enlargement and portal vein wall thickness. There was a negative correlation between IL-17 and the thickness of the portal vein wall, but more studies are necessary in order to explore the possible protective role of this cytokine. Despite the fibrosis group having presented a higher expression of pro-fibrotic molecules compared to WF/IFNE patients, it seems there is a regulation through IL-10 and T reg cells that is able to maintain the low morbidity of this group.